Optimization of Maximum Power Point Tracking (MPPT) Using P&O-Fuzzy and IC-Fuzzy Algorithms on Photovoltaic - Rido Octa Pratama; Machmud Effendy; Zulfatman Zulfatman (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Solar energy is energy which can be harnessed conveniently and free. However, its conversion result may not be easily obtained. Based on the previous research, solar power plant is a source of renewable energy, utilizing solar energy. Solar power plant converts solar energy into electricity using Photovoltaic (PV) or solar cells. Even though solar power plant is considered as better energy alternative, it presents problems and weaknesses. In this case, the problems are related to insufficient power generation with low power efficiency, high oscillation and very slow power tracking. Hence, in order to solve these problems, Maximum Power Point Tracking (MPPT) has been utilized. Combination method of P&O-fuzzy and IC-fuzzy is employed to its design. Moreover, combined algorithm may result better power from conventional algorithm due to appropriate performance of duty cycle according to system design, with efficiency result of 79%-85.6%, tracking in searching output power of 0,0055s - 0,008s, low oscillation and maximum power generated by combined algorithm of 1028 watt.